Young minds, deeper insights: a recap of the BMAS Summer School 2023, ranging from basic research to clinical implications of bone marrow adipose tissue - Amorim, Tânia; Trivanovic, Drenka; Benova, Andrea; Li, Hongshuai; Tencerova, Michaela; Palmisano, Biagio (Biology open, 2024)
Bone marrow adiposity (BMA) is a rapidly growing yet very young research field that is receiving worldwide attention based on its intimate relationship with skeletal and metabolic diseases, as well as hematology and cancer. Moreover, increasing numbers of young scientists and students are currently and actively working on BMA within their research projects. These developments led to the foundation of the International Bone Marrow Adiposity Society (BMAS), with the goal to promote BMA knowledge worldwide, and to train new generations of researchers interested in studying this field. Among the many initiatives supported by BMAS, there is the BMAS Summer School, inaugurated in 2021 and now at its second edition. The aim of the BMAS Summer School 2023 was to educate and train students by disseminating the latest advancement on BMA. Moreover, Summer School 2023 provided suggestions on how to write grants, deal with negative results in science, and start a laboratory, along with illustrations of alternative paths to academia. The event was animated by constructive and interactive discussions between early-career researchers and more senior scientists. In this report, we highlight key moments and lessons learned from the event.
Keywords: Schools; Bone marrow stromal cells; lidé; Bone Marrow; tuková tkáň; kostní dřeň; Adiposity; Adipocytes; Skeletal stem cells; Adipose Tissue; Career development; Young investigators; adipozita; školy; Humans